ACCEPTANCE AND USE OF TECHNOLOGY AND USER SATISFACTION OF THE DIGITALENT.KOMINFO.GO.ID WEBSITE: TERHADAP KEPUASAN PENGGUNA - Permassari, Katrina; Salamah, Ummi (Jurnal Studi Komunikasi dan Media, 2024)
The Ministry of Communication and Information Technology has implemented the Digital Talent Scholarship (DTS), which aims to improve the competence of Information and Communication Technology. This study explores the factors that influence the acceptance and use of the website and its impact on user satisfaction, specifically for the Vocational School Graduate Academy (VSGA) participants. This generation is considered to have good digital literacy, but field evidence shows that there are still challenges faced by DTS VSGA participants in accepting and using the digitalent.kominfo.go.id website. This study adopts the UTAUT 2 model to examine the factors that influence the acceptance and use of the website and measure its impact on user satisfaction with the digitalent.kominfo.go.id website. A quantitative approach was used, using a survey method with 356 respondents. Data analysis used Structural Equation Modeling (SEM) with the Partial Least Square (PLS) model. The study results indicate that the UTAUT 2 model only partially applies to accepting and using the digitalent.kominfo.go.id website. Based on the seven constructs in the UTAUT 2 model, only three variables—performance expectancy, social influence, and habit—influence behavioral intention. Usage behavior is directly influenced by behavioral intention and facilitating conditions, and usage behavior influences user satisfaction.